The effect of mobile health (mHealth) interventions on clinical outcomes and self-management behaviours in individuals with metabolic syndrome: a narrative review of evidence/ Maryam Hannah Daud, Fakhrul Hazman Yusoff and Anis Safura Ramli - Daud, Maryam Hannah; Yusoff, Fakhrul Hazman; Ramli, Anis Safura (Faculty of Medicine, 2023)
Introduction: There has been an exponential growth in mobile health (mHealth) technology for self-management of chronic conditions including metabolic syndrome (MetS). This narrative review aims to summarise the evidence on the effect of mHealth interventions on clinical outcomes and/or self-management behaviours among individuals with MetS or its components. Methods: Literature search for original research articles on mHealth for self-management of MetS or any of its components (type 2 diabetes mellitus, hypertension, dyslipidaemia, and obesity) from 2010-2021 was conducted using Web of Science, Scopus, PubMed, Cochrane Central Register of Controlled Trials, Google Scholar, SAGE and ScienceDirect. Keywords such as mHealth, effectiveness, self-management, MetS, hypertension, type 2 diabetes mellitus, dyslipidaemia and obesity were used. Articles in languages other than English, without access to full-text, outcomes unrelated to the effectiveness, and involved individuals aged <18 or >80 years old were excluded. All study designs were included except for study protocols. Results: A total of 184 potential papers were retrieved. Of these, 137 were excluded as they did not meet the inclusion/exclusion criteria. Consequently, 47 papers were included. Of these, 38 studies demonstrated effect of mHealth interventions in improving clinical outcomes (blood pressure, glycated haemoglobin, lipid profile, weight) and/or improvement in self-management behaviours (home blood pressure or blood sugar monitoring, exercise, diet or medication adherence) among individuals with MetS or its components. Only 12 studies were conducted in primary care. Apart from mHealth technologies, multifaceted elements such as doctor-patient interaction and wearable devices were also shown to be effective. Conclusion: This narrative review suggests that mHealth interventions may have positive effect on clinical outcomes and/or self-management behaviours among individuals with MetS and its components. This evidence should support development and evaluation of mHealth interventions to suit the needs of the Malaysian population, especially in primary care.